Uji Aktivitas Antioksidan Serta Formulasi Hard Lozenges Ekstrak Bunga Telang (Clitoria Ternatea L.) Dengan Variasi Perbandingan Laktosa – Manitol - Pujimagfiroh, Isnaini; Hartanto, Hartanto (Journal of Comprehensive Science, 2025)
Telang flower (Clitoria ternatea L.) is often used in traditional medicine because it is beneficial as an antioxidant. Hard Lozenges or suction tablets were chosen in this study because they are easy to use and have a sweet taste so it is expected that many people are interested in consuming. The purpose of this research was to be able to determine the antioxidant content in telang flower extract and to determine the formulation of Hard Lozenges telang flower extract with lactose – mannitol, which is the most optimal. The stages carried out in this study include the extraction of telang flower (Clitoria ternatea L.) and then tested for antioxidant activity using the DPPH method and then measured for absorbance with a UV spectrophotometer – Vis. Furthermore, for the formulation of Hard Lozenges, namely by the wet granulation method or wet granulation with variations in the ratio of lactose-mannitol additives, namely Formula 1 (1:0), Formula 2 (0:1), Formula 3 (1:1), Formula 4 (3:1), and Formula 5 (1:3). Furthermore, granule evaluation tests will be carried out on the five formulas, including moisture analyzer, flowability test, particle size test, and tap density test. After the granule evaluation test is carried out, then the granules are felt into Hard Lozenges or suction tablets which are then physically tested by the tablets including organoleptic test, hardness test, brittle test, weight diversity test, size uniformity test, and KLT test. The results of this study show that the formulation of Hard Lozenges of telang flower extract Formula 3 (F3), namely the variation of the Manitol – Lactose ratio of 1:1, is the most optimal formula compared to the other four variations of the formula.